ChemInform Abstract: Cascade [4 + 1] Annulation via More Environmentally Friendly Nitrogen Ylides in Water: Synthesis of Bicyclic and Tricyclic Fused Dihydrofurans. Issue 16 (28th March 2013) - Kumar, Atul; Srivastava, Suman; Gupta, Garima
Abstract The presented approach is the first one involving an in situ base regeneration for this type of reactions.